Executive Self-development that Affects the Excellence of the Organization - กำลังแพทย์ วรินทร์ทิพย์ (Academic Journal of North Bangkok University, 2020)
The research for the personal development of the manager and its effects for the most results of the organization had objectives 1) to study the personal development of the manager, 2) to study the exclusivity of the organization, and 3) to study the personal development of the manager and its effects towards the exclusiveness of the organization. The people used by this present research was conducted with an uncertain amount of people, hence the research team has an expectation from the total of people involved. With a reliance of 95% and accepting a fluctuation of 0.05 from the people involved. The calculation based on 384 people, using a specific sample program by Cochran (1953), the researchers collected results from 400 people, a tool used in collecting data was a questionnaire. Statistics used in data analysis were average, Standard Deviation, and Multiple Regression Analysis. Results revealed as follows: The analysis for the personal development of the manager in various ways with the results from evaluation, showed the majority of the characteristics has a satisfying results. Development in terms of general knowledge had a 3.74 percentage, development in terms of increasing knowledge and specialization with 3.82 percentage, personal development by helping oneself had a percentage of 3.96. Analyzing results in terms of organization exclusiveness in perspective of effectiveness, perspective in terms of service quality, perspective in terms of work force and perspective in terms of organization development, found that every perspective have good results. Perspective in terms of effectiveness had a 3.68 percent. Perspective in terms of service quality had a 3.69 percent, and perspective in terms of work force had a 3.58 percent and perspective in terms of organization development have a 3.53 percent. Analysis of executive self-development that affects the excellence of the organization by multiple regression analysis found that the results for general knowledge development factors only which could not predict the excellence of the organization (p-value .953). As for the factors of development of specific knowledge and skills and development factors by self-reliance could be able to predict the excellence of the organization.